Self-supporting nickel-molybdenum sulfide multistage nanosheet heterostructure catalyst as well as preparation method and application thereof
By growing nickel-molybdenum sulfide multi-stage nanosheet heterostructure catalyst in situ on nickel foam, the problem of poor stability of traditional powdered catalysts is solved, and the electrocatalytic performance with low total hydrolysis potential and high stability is achieved, and the overall energy conversion efficiency of hydrogen production by electrolyzing water is improved.
Patent Information
- Application Number
- CN202411901015.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-07
AI Technical Summary
Traditional powdered all-hydrolysis catalysts have poor stability during the process of electrolyzing hydrogen production, resulting in poor electrocatalytic performance, limiting the overall energy conversion efficiency of electrolyzing hydrogen production.
The nickel-molybdenum sulfide multi-stage nanosheet heterostructure catalyst is derived through a metal organic frame growing on nickel foam. The synergistic action of Ni3S2 and MoS2 is used to form a self-supporting electrode to improve the stability and electrocatalytic performance of the catalyst.
It achieves low total hydrolysis potential and high stability in an alkaline environment, improves the full hydrolysis electrocatalytic performance, and provides a reference for improving the performance of non-precious metal catalysts.
Smart Images

Figure CN119571385A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oxygen and hydrogen evolution electrocatalysts, and in particular to a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst and a preparation method and application thereof. Background Art
[0002] As non-renewable energy sources are becoming increasingly depleted, air pollution and ecological imbalance problems arise, and the development of renewable and environmentally friendly new energy sources is urgent. Among various new energy sources, hydrogen energy has attracted widespread attention for its advantages such as high energy density and pollution-free. Among the many hydrogen production technologies, water electrolysis is a method for preparing green hydrogen. It uses water as a raw material and has the advantages of being pollution-free and high in purity. Water electrolysis involves two half reactions, namely the anode oxygen evolution reaction (OER) and the cathode hydrogen evolution reaction (HER). Compared with the two-electron path of HER, OER undergoes a complex four-electron-proton coupling process, resulting in slow kinetics and requiring a higher energy barrier to be overcome, thus limiting the overall energy conversion efficiency of water electrolysis. Therefore, the development of efficient and stable hydrogen / oxygen evolution electrocatalysts is crucial to improving the efficiency of overall water splitting.
[0003] Metal-organic framework (MOFs) materials have the advantages of adjustable porosity, high specific surface area, and low price. They can be doped with elements or heterogenized through derivative processes such as ion exchange, carbonization, oxidation, sulfidation, and phosphiding to form a series of MOFs-derived transition metal catalysts. This type of catalyst can well inherit the excellent structural characteristics of MOFs precursors and exhibit good electrocatalytic activity. Among them, transition metal sulfides have attracted widespread attention due to their excellent catalytic activity, low price, and good corrosion resistance in alkaline electrolytes. However, metal-organic framework-derived sulfides have poor conductivity and are usually in powder form. When used as water electrolysis catalysts, binders are required to attach them to the electrode surface. With the generation of bubbles during hydrogen and oxygen evolution, the catalyst is easy to fall off, which greatly reduces the stability of the catalyst.
[0004] Therefore, providing a simple and easy method for synthesizing a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst to reduce the actual voltage of total hydrolysis and improve the stability of the catalyst is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0005] The present invention aims at the deficiencies of conventional powdered full hydrolysis catalysts, and provides a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst, a preparation method thereof, and an application thereof in full hydrolysis. The metal organic framework-derived nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst in situ grown on nickel foam obtained by the present invention inherits the morphology of the metal-benzenedicarboxylic acid framework well, utilizes the synergistic effect of trinickel disulfide and molybdenum disulfide, has a lower full hydrolysis potential in an alkaline environment, has better stability, and has broad application prospects in large-scale preparation of full hydrolysis catalysts.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst comprises the following steps:
[0008] (1) mixing a nickel nitrate solution and a terephthalic acid solution to obtain a transparent solution, adding the pretreated nickel foam to the transparent solution and heating the solution to obtain a precursor, i.e., nickel terephthalate in situ grown on the nickel foam;
[0009] (2) The precursor is added into an ammonium thiomolybdate solution and heated for reaction to obtain a Ni3S2-MoS2 / NF multi-level nanosheet heterostructure catalyst in situ grown on nickel foam.
[0010] The method of the invention is simple to operate and easy to implement, and can be extended to the design and synthesis of a series of composite materials with structural multifunctional advantages. During the sulfurization process, ammonium thiomolybdate is thermally decomposed into MoS2 and H2S, wherein H2S reacts with Ni-BDC to obtain Ni3S2. This hierarchical nanostructure uniformly composed of Ni3S2 and MoS2 has abundant heterogeneous interfaces, so that the active sites of Ni3S2 and MoS2 are fully exposed. This material can be used as a full hydrolysis electrocatalyst, and exhibits excellent HER, OER and full hydrolysis performance under alkaline conditions. The excellent electrochemical performance of Ni3S2 / MoS2 / NF is mainly attributed to its multi-level nanosheet heterostructure, the synergistic effect between Ni3S2 and MoS2, and the stability of the self-supporting electrode.
[0011] Preferably, the solvent of the nickel nitrate solution and the terephthalic acid solution in step (1) is N,N-dimethylformamide;
[0012] The molar ratio of the nickel nitrate to the terephthalic acid is 4:3.
[0013] Preferably, the molar volume ratio of nickel nitrate to N,N-dimethylformamide in the nickel nitrate solution is 1 mmol:5 mL;
[0014] The molar volume ratio of terephthalic acid to N,N-dimethylformamide in the terephthalic acid solution is 0.75mmol:5mL.
[0015] Preferably, a sodium hydroxide solution is also added to the terephthalic acid solution in step (1), and the molar ratio of the sodium hydroxide to the terephthalic acid is 0.002-0.004:0.75.
[0016] Since the ionization degree of the carboxyl group (-COOH) of the terephthalic acid ligand is limited under acidic or neutral conditions, the present invention can increase the pH of the solution by adding sodium hydroxide (NaOH) to promote the ionization of the carboxyl group of terephthalic acid to -COOH - This deprotonated ligand is more conducive to Ni 2+ Ions undergo coordination reactions.
[0017] Preferably, the concentration of the sodium hydroxide solution is 4 mol / L.
[0018] Preferably, the heating reaction conditions in step (1) are: heating at 100° C. for 15 h.
[0019] Preferably, the pretreatment step in step (1) is: ultrasonically remove the surface oxide of the nickel foam in hydrochloric acid, ethanol and water in sequence, and then take it out and vacuum dry it.
[0020] Preferably, the ultrasonication time is 15 min.
[0021] Preferably, the heating reaction in step (1) to obtain the precursor further comprises washing with ethanol and water alternately for 3 times, and then drying;
[0022] Preferably, the solvent of the ammonium thiomolybdate solution in step (2) is N,N-dimethylformamide;
[0023] The molar ratio of the ammonium thiomolybdate to the nickel nitrate is 0.1-0.6:1.
[0024] Preferably, the molar volume ratio of ammonium thiomolybdate and N,N-dimethylformamide in the ammonium thiomolybdate solution is 0.4 mmol:10 mL.
[0025] Preferably, the heating reaction conditions in step (2) are: heating at 200° C. for 20 h.
[0026] Preferably, the heating reaction to obtain the product in step (2) further comprises washing the product with ethanol and water alternately for three times, and then drying the product.
[0027] A self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst is obtained by the preparation method described above.
[0028] The application of a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst obtained by the preparation method described above in the field of water electrolysis.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The present invention in situ grows a metal organic framework on nickel foam and hydrothermally sulfurizes it to obtain a Ni3S2-MoS2 / NF catalyst with a multi-level nanosheet heterostructure. The preparation method is simple and easy to operate.
[0031] (2) The catalyst Ni3S2-MoS2 / NF prepared in the present invention is used as a full hydrolysis catalyst. Thanks to its multi-level nanosheet heterostructure and the interaction between the Ni3S2 and MoS2 phases, the full water splitting electrocatalytic performance is further improved.
[0032] (3) The product obtained by the method of the present invention has better catalytic performance as a complete water splitting electrocatalyst compared with catalysts such as RuO2 and Pt / C precious metals, providing a reference for improving the performance of non-precious metal catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. The drawings in this description are only embodiments of the present invention.
[0034] Figure 1 This is a scanning electron microscope image of the Ni-BDC / NF of the present invention;
[0035] Figure 2 This is a scanning electron microscope image of Ni3S2-MoS2 / NF of the present invention;
[0036] Figure 3 X-ray powder diffraction patterns of Ni-BDC / NF, Ni3S2 / NF, MoS2 / CC and Ni3S2-MoS2 / NF of the present invention;
[0037] Figure 4 It is the Raman image of Ni3S2-MoS2 / NF-4 of the present invention;
[0038] Figure 5 It is the performance curve diagram of Ni-BDC / NF, Ni3S2 / NF, MoS2 / CC and Ni3S2-MoS2 / NF of the present invention;
[0039] Figure 6It is the electrocatalytic total hydrolysis polarization curve diagram of RuO2║Pt / C and Ni3S2-MoS2 / NF║Ni3S2-MoS2 / NF of the present invention and the stability test curve diagram of Ni3S2-MoS2 / NF║Ni3S2-MoS2 / NF. DETAILED DESCRIPTION
[0040] Embodiments of the present invention are described below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but are not to be construed as limiting the present invention.
[0041] Example 1
[0042] The present invention provides a method for preparing a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst, comprising the following steps:
[0043] (1) Cut the nickel foam (1*3cm 2 ) ultrasonically in 3M hydrochloric acid, ethanol and water for 15 min respectively to remove the oxide on the surface of the nickel foam, and then place the treated nickel foam on the surface and vacuum dry it at 60°C for later use;
[0044] (2) First, weigh 1 mmol of Ni(NO3)2·6H2O and dissolve it in 5 mL of DMF and stir it evenly to obtain a nickel nitrate solution. Then, weigh 0.75 mmol of H2BDC and dissolve it in 5 mL of DMF. Then, add 1 mL of 4.0 M NaOH solution and stir it evenly to obtain a terephthalic acid solution.
[0045] The uniformly stirred nickel nitrate solution was added dropwise to the terephthalic acid solution and magnetically stirred until the solution was transparent. The mixture was then transferred to a 25 mL reactor and a piece of nickel foam (1*3 cm 2 ) was added to the obtained mixture, and an autoclave was assembled, and the mixture was placed in a forced air drying oven, and kept at 100° C. for 15 h. After the heat preservation was completed, the mixture was naturally cooled to room temperature. The obtained sample was washed alternately with ethanol and water for 3 times, and dried at 60° C. to obtain nickel benzene dicarboxylate (Ni-BDC / NF) in situ grown on nickel foam as a precursor;
[0046] (3) 0.4 mmol of ammonium thiomolybdate powder was completely dissolved in 10 mL of DMF and stirred to obtain a thiomolybdic acid solution; the thiomolybdic acid solution was then poured into a 25 mL reactor, and the Ni-BDC / NF precursor obtained in step (2) was added, and the autoclave was placed in a forced air drying oven and reacted at 200° C. for 20 h. After the reaction was completed, the reaction was naturally cooled to room temperature, and the obtained sample was washed alternately with ethanol and water for 3 times, and dried at 60° C. to obtain a Ni3S2-MoS2 / NF-4 multi-level nanosheet heterostructure catalyst grown in situ on nickel foam.
[0047] Comparative Example 1
[0048] The present invention provides a method for preparing a catalyst, comprising the following steps:
[0049] (1) The preparation method of the precursor Ni-BDC / NF is the same as that in the embodiment;
[0050] (2) Weigh 40 mg of thiourea powder and completely dissolve it in 10 mL of DMF, stir it evenly, and obtain a thiourea solution; then, pour the thiourea solution into a 25 mL reactor, add the Ni-BDC / NF precursor obtained in step (1), put the autoclave into a forced air drying oven, react at 200° C. for 20 h, and naturally cool to room temperature after the reaction is completed. The obtained sample is washed alternately with ethanol and water for 3 times, and dried at 60° C. to obtain a Ni3S2 / NF catalyst grown in situ on nickel foam.
[0051] Comparative Example 2
[0052] The present invention provides a method for preparing a catalyst, comprising the following steps:
[0053] (1) The carbon cloth (CC) was ultrasonically cleaned with acetone and 0.5 M H2SO4 for 10 min, then washed with distilled water to remove residual chemicals, and dried at 100°C for later use;
[0054] (2) 0.4 mmol of ammonium thiomolybdate powder is completely dissolved in 10 mL of DMF and stirred to obtain a thiomolybdic acid solution; then, the thiomolybdic acid solution is poured into a 25 mL reactor, and the CC treated in step (1) is added, and the autoclave is placed in a forced air drying oven and reacted at 200° C. for 20 h. After the reaction is completed, the sample is naturally cooled to room temperature, and the obtained sample is washed alternately with ethanol and water for 3 times, and dried at 60° C. to obtain a MoS2 / CC catalyst.
[0055] The scanning electron microscope image of Ni-BDC / NF obtained in Example 1 is as follows: Figure 1 As shown in a and b in the figure, it can be seen that the Ni-BDC / NF prepared by the solvothermal method has a flaky structure, a smooth surface, and grows evenly on the nickel foam;
[0056] The scanning electron microscope image of Ni3S2-MoS2 / NF-4 obtained in Example 1 is as follows Figure 2 As shown in a and b, it can be seen from the figure that Ni3S2-MoS2 / NF-4 inherits the nanosheet morphology of Ni-BDC / NF very well, and grows wrinkled nanoflowers on the surface of the original nanosheet to form a multi-level nanosheet structure;
[0057] The X-ray powder diffraction of Ni-BDC / NF obtained in Example 1 is as follows: Figure 3As shown in a, it can be seen from the figure that the diffraction peak of the Ni-BDC / NF precursor is in good agreement with the simulated crystal structure diagram, proving the successful preparation of Ni-BDC / NF;
[0058] The X-ray powder diffraction of Ni3S2-MoS2 / NF-4 obtained in Example 1 is as follows: Figure 3 As shown in b, it can be seen from the figure that the diffraction peaks of Ni3S2-MoS2 / NF-4 multi-level nanosheets on nickel foam are similar to those of Ni3S2 / NF, corresponding to the standard card of Ni3S2, but no diffraction peaks of MoS2 are found, which may be due to the low content of MoS2 or low crystallinity in the product;
[0059] The Raman spectrum of Ni3S2-MoS2 / NF-4 obtained in Example 1 is as follows Figure 4 As shown in the figure, it can be seen that: at 350cm -1 and 200cm -1 The Raman peak at 320 cm is the vibration mode of Ni3S2. -1 and 150cm -1 The peaks on the left and right are the characteristic peaks of 1T phase MoS2; at the same time, at 404cm -1 and 373cm -1 The Raman peaks at 800-1000 cm-1 correspond to the in-plane (E12g) and out-of-plane (A1g) vibration modes of the Mo-S bond in 2H-MoS2. -1 The three obvious peaks at the edge sites of MoS2 are related to the [Mo3S 13 ] 2- Material related;
[0060] Figure 5 Performance curves of Ni-BDC / NF, Ni3S2 / NF, MoS2 / CC and Ni3S2-MoS2 / NF, where a is the OER polarization curve, b is the Tafel plot, and c is the chronoamperometric curve, with the inset being Ni3S 2- Polarization curves of MoS2 / NF-4 before and after 1000CV cycles, d is the HER polarization curve, e is the Tafel diagram, and f is the chronoamperometric curve. The inset is Ni3S 2- Polarization curves of MoS2 / NF-4 before and after 1000CV cycles. It can be seen from the figure that in 1M KOH, Ni3S2-MoS2 / NF-4 has a high conductivity at 100mA cm -2 At a current density of 1.3 Å, the oxygen evolution reaction only requires an overpotential of 216 mV, and the hydrogen evolution reaction only requires an overpotential of 165 mV, indicating that in situ growth on nickel foam is conducive to charge transfer, and the rich heterogeneous interface can expose a large number of active sites, showing excellent electrocatalytic performance.
[0061] Figure 6 The electrocatalytic full hydrolysis polarization curve and stability test curve of Ni3S2-MoS2 / NF-4║Ni3S2-MoS2 / NF-4 prepared by the product obtained in Example 1, wherein a is the electrocatalytic full hydrolysis polarization curve, and b is the stability test curve. It can be seen from the figure that in 1M KOH, the two-electrode system composed of Ni3S2-MoS2 / NF-4 is 100mA cm -2 Only a potential of 1.64 V is required at a current density of 1.5 V, and there is no obvious attenuation of the current density after 750 h of reaction, indicating that Ni3S2-MoS2 / NF-4 has excellent full hydrolysis performance and ultra-high stability, and has good application prospects.
[0062] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst, characterized in that: The following steps are involved: (1) mixing a nickel nitrate solution and a terephthalic acid solution to obtain a transparent solution, adding the pretreated nickel foam to the transparent solution and heating the solution to obtain a precursor, i.e., nickel terephthalate in situ grown on the nickel foam; (2) The precursor is added into an ammonium thiomolybdate solution and heated for reaction to obtain a Ni3S2-MoS2 / NF multi-level nanosheet heterostructure catalyst in situ grown on nickel foam.
2. The method for preparing a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst according to claim 1, characterized in that: The solvent of the nickel nitrate solution and the terephthalic acid solution in step (1) is N,N-dimethylformamide; The molar ratio of the nickel nitrate to the terephthalic acid is 4:
3.
3. The method for preparing a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst according to claim 1, characterized in that: In step (1), a sodium hydroxide solution is also added to the terephthalic acid solution, and the molar ratio of the sodium hydroxide to the terephthalic acid is 0.002-0.004:0.
75.
4. The method for preparing a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst according to claim 3, characterized in that: The concentration of the sodium hydroxide solution is 4 mol / L.
5. The method for preparing a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst according to claim 1, characterized in that: The heating reaction conditions in step (1) are: heating at 100° C. for 15 h.
6. The method for preparing a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst according to claim 1, characterized in that: The pretreatment step in step (1) is as follows: ultrasonically remove the surface oxide of the nickel foam in hydrochloric acid, ethanol and water in turn, and then take it out and vacuum dry it.
7. The method for preparing a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst according to claim 1, characterized in that: The solvent of the ammonium thiomolybdate solution in step (2) is N,N-dimethylformamide; The molar ratio of the ammonium thiomolybdate to the nickel nitrate is 0.1-0.6:
1.
8. The method for preparing a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst according to claim 1, characterized in that: The heating reaction conditions in step (2) are: heating at 200° C. for 20 h.
9. A self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst obtained by the preparation method according to any one of claims 1 to 8.
10. Application of a self-supporting nickel-molybdenum sulfide multi-level nanosheet heterostructure catalyst obtained by the preparation method according to any one of claims 1 to 8 in the field of water electrolysis.